ECBP: an energy efficient cross layer cluster based routing protocol for improved multimedia data dissemination in VANETs - Shafi, Shaik; V R, Devanaboyina; N. Bhandari, B (International Journal of Engineering and Technology, 2018)
Vehicular Ad hoc network (VANET) is an infrastructure less decentralized dynamic network, offers safety and multimedia applications. To strengthen these services, VANET demands networking of high data packets among fast moving vehicles with less link breaks. In this paper, â€œAn Energy Efficient Cross layer Cluster Based Routing Protocol (ECBP) for Improved Multimedia Data Dissemination in VANETsâ€ is proposed. Design of ECBP with energy efficient is achieved by considering (i) mobility metrics such as Residual distance and Relative velocity to group the vehicles into clusters reduces unnecessary flooding of control beacons (ii) Neighborhood knowledge, identifies adaptive relay vehicle reduces delay. Simulation results using Network Simulator (NS) -2.34 indicate that the proposed ECBP improves throughput of multimedia data with reduced energy consumption for different vehicle density in comparison with existing VANET cross layer based routing approach. Â Â